Substance use and its determinants among students of industrial training institute in tribal area of Thane district, Maharashtra - Acharya, Shrikala; Chandrachood, Mandar V. (International Journal Of Community Medicine And Public Health, 2020)
Background: Substance use is a major public health challenge because it is engulfing the younger generation with serious health, social and economic concern. Unhealthy behaviors such as smoking, drinking and illicit drug use often begin during adolescence. The study was undertaken with objectives of assessing the prevalence of substance use and its determinants among students of Industrial Training Institute (ITI). Methods: A cross sectional study was conducted in all students of the institute to find out prevalence of substance use and its determinants. Data was collected in a predesigned and pretested proforma by oral questionnaire method and was analyzed by SPSS software using descriptive statistics and appropriate statistical tests of significance. Results: Prevalence of substance use was 18%. There was no significant association of substance use with age, education, caste or residence of the student but it was significantly associated with type of family (p=0.02) and literacy of mother and father (p=0.04 and p=0.01). Tobacco was most commonly used substance and most common factor determining substance use was addiction in family members. All the participants were aware about cancer as a health hazard of substance use but awareness about other health hazards was low. Conclusions: Several factors can act as determinants of substance use including type of family, education of parents, peer pressure and addiction in family members. Role of family and society should be identified and practiced for prevention and control of this substance use.